Alimentação de Serrasalmus maculatus (Kner, 1858) (characiformes; serrasalmidae) no trecho inferior bacia do rio Sorocaba, São Paulo, Brasil - Villares Jr., Gilberto Aparecido [UNESP]; Gomiero, Leandro Muller [UNESP]; Goitein, Roberto [UNESP] (Universidade Estadual de Maringa, 2008)
The aim of this study was to discuss aspects of the diet of Serrasalmus maculatus. Fish were collected using gill nets, whose lengths measured 100 m and mesh diameters varied from 3 to 8 cm. A total of 107 individuals were collected. Their length varied from 62 to 210 mm. They were mainly represented by female and immature individuals. No individual was caught in temperatures below 21°C. Four feeding item categories were observed: fish muscle pieces, parts of fish fins, plant fragments, and insects. Comparisons made among individual length classes revealed some significant differences within stomach consumed contents. Individuals whose length exceeded 165 mm consumed only parts of fish muscles and plants. The food availability in the environment and the class lengths amplitude may, however, have influenced the results, in which ontogenetic differences should not be precisely observed.
Feeding of Serrasalmus maculatus (Kner, 1858) (characiformes; serrasalmidae) in the Sorocaba river, São Paulo State, Brazil
Keywords: Diet; Piranhas; Predation; Sorocaba river